2008
DOI: 10.1136/gut.2007.135665
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin plays a protective role in caerulein-induced acute pancreatitis in mice fed a high-fat diet

Abstract: Adiponectin plays a protective role in caerulein-induced AP in HFD-fed mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 33 publications
3
42
0
2
Order By: Relevance
“…Also, in our study, rats treated with exendin-4 had lower insulin, adiponectin and leptin levels than control rats. Previous studies have found that adiponectin possibly plays a protective role in acute pancreatitis [21]. In our study, we found that the rats treated with exendin-4 had lower serum adiponectin than control rats, albeit not statistically significant.…”
Section: Effect Of Exendin-4 On Pancreatic Cellssupporting
confidence: 58%
“…Also, in our study, rats treated with exendin-4 had lower insulin, adiponectin and leptin levels than control rats. Previous studies have found that adiponectin possibly plays a protective role in acute pancreatitis [21]. In our study, we found that the rats treated with exendin-4 had lower serum adiponectin than control rats, albeit not statistically significant.…”
Section: Effect Of Exendin-4 On Pancreatic Cellssupporting
confidence: 58%
“…Furthermore, in AP patients, serum adiponectin levels were inversely correlated with organ dysfunction. However, other studies detected no significant differences in serum adiponectin concentrations [2,3,10,11,12,21]. …”
Section: Discussionmentioning
confidence: 93%
“…It has anti-inflammatory properties in addition to various biological functions, and low serum adiponectin levels are present in obesity [9]. Adiponectin plays a protective role in cerulein-induced AP [6,10,11]. Hypoadiponectinemia could enhance the severity of pancreatitis [12].…”
Section: Introductionmentioning
confidence: 99%
“…Some sections were stained with H&E or sirius red (to visualize collagen deposition) by using standard techniques. Immunostaining for a-SMA and F4/80 was performed as described previously [1], using antibodies against a-SMA (Dakocytomation) and F4/80 (Serotec).…”
Section: Reagentsmentioning
confidence: 99%
“…We reported previously that adiponectin deficiency enhanced the severity of cerulein-induced acute pancreatitis in mice fed a high-fat diet [1]. Moreover, obesity was recently reported to be an independent risk factor for certain pancreatic diseases such as pancreas cancer [2] and acute pancreatitis [3].…”
Section: Introductionmentioning
confidence: 97%